2016
DOI: 10.1097/md.0000000000005366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute kidney injury on coagulation in adult minimal change nephropathy

Abstract: A hypercoagulable state exists in patients with nephrotic syndrome (NS), which more easily leads to venous thromboembolism (VTE). However, whether acute kidney injury (AKI), a common complication of NS, affects the hypercoagulable state and VTE has rarely been elucidated. In this study, we aimed to explore coagulation changes and analyze relevant influencing factors in NS-AKI patients.A total of 269 consecutive NS patients with minimal change disease (MCD) between 2011 and 2016 were included in this observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…(4)(5)(6) Recently, similar hemostatic alterations have been described in patients with AKI without chronic liver disease. (7)(8)(9)(10) AKI is a relatively common complication of decompensated cirrhosis, occurring in approximately 20% of hospitalized patients, (11) and may be associated with an increased risk of bleeding. (3,12,13) However, the effect of AKI on the hemostatic system in patients with cirrhosis has not yet been fully investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(4)(5)(6) Recently, similar hemostatic alterations have been described in patients with AKI without chronic liver disease. (7)(8)(9)(10) AKI is a relatively common complication of decompensated cirrhosis, occurring in approximately 20% of hospitalized patients, (11) and may be associated with an increased risk of bleeding. (3,12,13) However, the effect of AKI on the hemostatic system in patients with cirrhosis has not yet been fully investigated.…”
mentioning
confidence: 99%
“…( 4‐6 ) Recently, similar hemostatic alterations have been described in patients with AKI without chronic liver disease. ( 7‐10 )…”
mentioning
confidence: 99%
“…Increased levels of FIB result in an increase in blood viscosity, leading to shear stress damage in endothelial cells (18). Studies have shown that FIB in tissues is significantly elevated in acute kidney injury caused by ischemia-reperfusion (19)(20)(21). FIB causes severe renal dysfunction by increasing renal fibrosis (22).…”
Section: Discussionmentioning
confidence: 99%
“… 3 Indeed, several studies have described adult minimal change nephropathy complicated by pulmonary embolism. 22 24 Furthermore, adult patients with minimal change disease complicated by acute kidney injury, which are seen more frequently in older adults than in younger patients, 25 may have a severe hypercoagulable state. 24 The favorable decline in the serum Cr level along with a reduction in the urine protein level in the current patient implies the concurrent reversible acute kidney injury despite the lack of objective time course data indicating the functional status before the onset of NS.…”
Section: Discussionmentioning
confidence: 99%
“… 22 24 Furthermore, adult patients with minimal change disease complicated by acute kidney injury, which are seen more frequently in older adults than in younger patients, 25 may have a severe hypercoagulable state. 24 The favorable decline in the serum Cr level along with a reduction in the urine protein level in the current patient implies the concurrent reversible acute kidney injury despite the lack of objective time course data indicating the functional status before the onset of NS. Finally, the low rate of reported adverse events with anticoagulation as well as our patient’s markedly decreased serum Alb levels encouraged us to pursue heparinization prior to the renal biopsy as practiced empirically.…”
Section: Discussionmentioning
confidence: 99%